Cognitive disorders in epilepsy I: Clinical experience, real-world evidence and recommendations. (December 2020) - Kanner, Andres M.; Helmstaedter, Christoph; Sadat-Hossieny, Zahra; Meador, Kimford
Highlights: Cognitive disorders are a common comorbidity in children and adults with epilepsy. They are under-identified and frequently not treated. Cognitive disturbances may preceed the onset of seizures and are multifactorial. ADHD and depression are associated with a worse academic performance. The use of CNS stimulants and SSRI antidepressants are safe in patients with epilepsy. Abstract: This is the first of two narrative reviews on cognitive disorders in epilepsy (companion publication : Cognitive disorders in epilepsy II: Clinical targets, indications and selection of test instruments). Its focus is on clinical experience, real-world evidence, and clinical recommendations. Cognitive disorders are a common comorbidity in children and adults with epilepsy. These cognitive disturbances may preceed the onset of seizures and are multifactorial including contributions by pre-existing brain damage, seizures, interictal epileptic discharges, and treatments including medications and surgery. Comorbid cognitive impairments can have a negative impact on the quality of life in people with epilepsy. They are under-identified and frequently not treated. Comorbid psychiatric disorders, such as ADHD can also contribute to a worse cognitive performance and can benefit from pharmacotherapy with CNS stimulants. Likewise, mood disorders cause a subjective perception of poor memory and attention, which can be reversed with antidepressants of the SSRI family. This narrative review discusses these issues from a real-world clinical perspective in children and adults with newly diagnosed and chronic epilepsy. The need for further research to understand and treat these disorders is noted.